PENINGKATAN AKTIFITAS PESERTA DIDIK DALAM PEMBELAJARAN PKn MELALUI METODE JIGSAW DI KELAS XII IPS2 SMAN 1 SULIKI KABUPATEN LIMA PULUH KOTA - Nurlaila, Nurlaila (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
This Classroom Action Research aims to increase the activity of learners in the learning of Citizenship Education classroom XII2 IPS at SMA Negeri 1 of Suliki Subdistrict, the District Lima Puluh Kota in the 1st half semester of 2011/2012 academic year through the application of the Jigsaw method of cooperative learning techniques. This study was conducted in two cycles. The results of this study showed an increase in activity of the learner, the average value of learning outcomes, and learning completeness of learners. The conclusion of this study is that there are increased activities in the learning of learners in Citizenship Education by using the Cooperative Learning Jigsaw techniques so as to improve learning outcomes in class XII2 IPS SMA Negeri 1 of Suliki Subdistrict, the District of Limapuluh Kota. Key Words: Learning activity, learners, jigsaw method